Productivity, chemical composition and In situ ruminal degradation kinetics of Morus alba at diferent regrowth ages - Torres-Navarrete, E.; Sánchez-Laiño, A.; Espinoza-Guerra, I.; Barrera-Alvarez, A.; Verdecia, D. M.; Ramírez, J. L.; Herrera, R. S. (Cuban Journal of Agricultural Science, 2019)
Using a random block design and four replications with six treatments consisting on regrowth ages (30, 45, 60, 75, 90 and 105 days), their biomass production, dry matter, chemical composition and In situ ruminal degradation kinetics of Morus alba, was evaluated in la María, Los Ríos, Ecuador. It was sampled in plots of 1,200 m2, in which a uniformity cut was applied at 0.5 m high over the soil level, without using irrigation or fertilization. Edible biomass, DMY, DM, CP, NDF, ADF and OM were determined, as well as In situ ruminal degradation kinetics (DM, NDF and OM). There were increases of dry matter and edible biomass production of 1.77 and 0.45 t/ha-1, respectively, as well as 7.5, 11.21 and 18.28 percent units for DM, NDF and ADF, while there was a decrease for CP and OM of 4.99 and 8.44 percent units, respectively up to 105 days. For degradation kinetics of dry matter, the best results were obtained at 30 days with 81.24 %, 7.08 %, 0.41 %/h, 88.32 %, 66.06 %, 63.78 %, and 61.5 1% for soluble fraction (a), potentially degradable (b), degradation rate (c), potential degradability (a+b) and effective degradability at ruminal passage rate of 2, 5 and 8 %, respectively. This same performance was maintained for OM and NDF. It can be concluded that regression equations were established, which explain the close relation among age, edible biomass production and dry matter. Dry matter and crude protein values were lower than those reported for this species in the international literature for production systems in tropical areas. These differences could be attributed to the zero use of irrigation and fertilization during the research. It is important to highlight that soluble fraction, potential and effective degradation of DM, OM and NDF were maintained with values superior to 50 %. Further studies are suggested in other periods of the year, cut height, phytochemical composition, intake tests and animal response. Key words: shrubs, biomass, effective digestion, age, regrowth, mulberry